Is the Motor System Necessary for Processing Action and Abstract Emotion Words? Evidence from Focal Brain Lesions - Dreyer, Felix R.; Frey, Dietmar; Arana, Sophie; Saldern, Sarah von; Picht, Thomas; Vajkoczy, Peter; Pulvermüller, Friedemann (Frontiers in Psychology, 2015)
Neuroimaging and neuropsychological experiments suggest that modality-preferential cortices, including motor- and somatosensory areas contribute to the semantic processing of action related concrete words. In contrast, a possible role of modality-preferential – including sensorimotor – areas in processing abstract meaning remains under debate. However, recent fMRI studies indicate an involvement of the left sensorimotor cortex in the processing of abstract-emotional words (e.g. “love”). But are these areas indeed necessary for processing action-related and abstract words? The current study now investigates word processing in two patients suffering from focal brain lesion in the left frontocentral motor system. A speeded lexical decision task (LDT) on meticulously matched word groups showed that the recognition of nouns from different semantic categories – related to food, animals, tools and abstract-emotional concepts – was differentially affected. Whereas patient HS with a lesion in dorsolateral central sensorimotor cortex next to the hand area showed a category-specific deficit in recognizing tool words, patient CA suffering from lesion centered in the left SMA was primarily impaired in abstract-emotional word processing. These results point to a causal role of the motor cortex in the semantic processing of both action-related object concepts and abstract-emotional concepts and therefore suggest that the motor areas previously found active in action-related and abstract word processing can serve a meaning-specific necessary role in word recognition. The category-specific nature of the observed dissociations is difficult to reconcile with the idea that sensorimotor systems are somehow peripheral or ‘epiphenomenal’ to meaning and concept processing. Rather, our results are consistent with the claim that cognition is grounded in action and perception and based on distributed action perception circuits reaching into sensorimotor areas.